NILAI PENDIDIKAN KARAKTER PADA KARAKTER UTAMA DALAM FILM THE LION KING - Lavio Bintang Desta (Yayasan Nusantara Hasana Berdikari, 2024)
Films are closely related to people's daily lives and are easily accessible to most people. Furthermore, films can convey ideas, experiences and thoughts through the images and sounds they present, and can captivate the hearts and emotions of the audience. This research aims to analyze the educational value of Simba, a character in the film The Lion King (1994). This research is a qualitative descriptive research that analyzes data using text analysis, and data that can be obtained by treating film format data as text. Based on research results, ``The Lion King'' (1994) contains all the character education values ​​recommended by the Ministry of Education and Culture. These values ​​are displayed at various times along with nine characters at the beginning of the film, namely religious, tolerant, disciplined, independent, hardworking, cooperative, collegial, responsible and honest, there are 11 characters who are the center of attention in the film. Honest, nature-loving, peace-loving, patriotic, creative, tough, appreciative, honest, loyal, integrative, nationalist. These results prove that the film The Lion King (1994) is a good children's film and suitable for educational purposes.